Effects of restraining method with or without stunning on the physicochemical properties of broiler breast and thigh muscles - Ismail, Siti Nadirah; Sazili, Awis Qurni; Idrus, Zulkifli; Goh, Yong Meng; Mohamed, Elmutaz Atta Awad; Mohd Zulkifli, Nur Afzanisa (Faculty of Animal Husbandry, Brawijaya University, 2017)
A study was conducted to determine the effects of restraint and stunning methods on the physicochemical properties of Pectoralis major (breast) and Iliotibialis (thigh) muscles of broiler chickens. Sixty Cobb 500 broilers were randomly assigned to a 2 × 2 factorial arrangement in a completely randomized design with 15 birds in each treatment group. The birds were assigned to two restraint methods (shackle and cone) and two stunning methods (unstunned and stunned). Samples of breast and thigh muscles at 24 h postmortem were analyzed for pH, drip and cooking loss, shear force, and color. Meat pH and color of breast muscle were significantly (P<0.05) affected by the restraint method. Shackled restrained birds had lower breast meat pH, redness, and yellowness compared to cone restrained birds. However, none of the physicochemical properties of thigh muscle was affected by restraint method. The results demonstrate that restraint and stunning methods affect meat pH and color values of broiler breast muscle but did not affect the physicochemical properties of thigh muscle.